PENGENALAN NILAI MATA UANG BAGI SISWA AUTIS DENGAN MEMODIFIKASI MONOPOLI - Marhamah; Ratu Ilma Indra Putri; Zulkardi; Yusuf Hartono (Jurnal Berdaya Mandiri, 2025)
In Indonesia, the right to education for children with special needs has been regulated in the Law, this shows that the opportunity to obtain education is a right that must be fulfilled by the state, without exception for children with special needs, one of which is autism. Autism is also called autism spectrum disorder because even though it has varying symptoms, these symptoms are under the same umbrella of problems, namely social interaction, communication and behavior. In self-development of autistic children, there are work skills which discuss recognizing the value of currency well and one of the therapies that can be done for autistic children is play therapy. The monopoly game is an alternative to introduce the value of currency to autistic students by modifying the monopoly according to the needs of autistic students. The activity was attended by 79 participants and was carried out online. At the end of the activity, participants were able to understand how to introduce the value of currency to autistic students through games using the PMRI approach. Keyword: autism, monopoly, currency value